Dispositional mindfulness and BIS/BAS up-close: can the self-regulation of people be seen in the eyes? - Valachová, Michaela; Lisá, Elena (Frontiers in Psychology, 2023)
Pigmentation in animal models is related to behavioral regulation and development (Trut et al., 2004), suggesting that both may belong to the same biological system. However, such models are poorly documented in humans. The current study explored personality and group differences in self-regulation among healthy subjects and their specific eye structures (contraction furrows and pigment spots). Three objectives were proposed: To analyze statistical differences in dispositional mindfulness (DM), behavioral inhibition system (BIS), and behavioral approach system (BAS) among subjects with a specific iris type of contraction furrows and pigment spots. The study sample consisted of 194 university students. One month after taking photographs of their eyes, the students completed the online scales of DM, BIS, and BAS. DM was negatively related to pigment spots (rs = -.193; p < .01). Cluster analysis of the iris structures converged at a four-cluster solution. The cluster types 2 (absence of pigment spots and contraction furrows extending 8/10 of iris circle or more) and 3 (one or more pigment spots and contraction furrows extending 8/10 of iris circle or more) significantly differed in DM with a small effect size (F = 3.37; p = .021; η² = 0.051). Participants with contraction furrows (8/10 or more circle extent) and without pigment spots had a significantly higher DM than those with pigment spots. No significant differences existed among the iris types in BIS/BAS. Future research directions are suggested.